Literature Review : Implementasi Model Pembelajaran PjBL guna Meningkatkan Keterampilan Berpikir Kreatif Peserta Didik pada Pembelajaran Biologi - Forendra, Salsabilla; Selaras, Ganda Hijrah (YASIN, 2023)
One of the higher thinking skills is creative thinking skills. Indonesia was ranked 74th out of 79 countries in the 2018 PISA results. These findings show the importance of developing one's creative thinking skills while studying. The aim of this article is to see how far PjBL can be applied to creative thinking. Utilizing digital libraries such as Google Scholar and Crossref, a prism-style Systematic Literature Review is the preferred approach. To obtain scientific articles about science learning in the biology sub-chapter published in 2018–2023, the Systematic Review is used to synthesize various relevant studies. The findings show that the PjBL model can improve science learning in the biology sub-sector by increasing critical thinking, communication, collaboration, creativity, and innovation (4C), as well as learning outcomes, communication, concepts and understanding.